Characterization of the englacial and subglacial drainage system in a high Arctic cold glacier by speleological mapping and ground-penetrating radar - Temminghoff, M.; Benn, D. I.; Gulley, J. D.; Sevestre, H. (Geografiska Annaler: Series A, Physical Geography, 2019)
© 2018, © 2018 Swedish Society for Anthropology and Geography. This paper presents new data obtained by speleological surveys and ground-penetrating radar (GPR) on a cut-and-closure conduit in Scott Turnerbreen, a small cold glacier in Svalbard, Norwegian Arctic. We use these data to propose criteria for the identification of cut-and-closure conduits from GPR data. In addition, we describe subglacial and englacial structures exposed in the conduit, which shed light on the former dynamic behaviour of the glacier. The glacier bed consists of a thick layer of subglacial traction till, from which till-filled fractures extend upward into the ice. These observations show that Scott Turnerbreen was formerly warm-based, and are consistent with a surge or surge-like behaviour. The channel system was also imaged using GPR. Varying channel morphologies have distinctive signatures on GPR profiles, allowing the identification and mapping of englacial drainage systems in situations where direct access is impossible.